(untitled) (Research, Society and Development, 2022)
Public health emergencies call into question the practicability of precepts governed by human rights in vulnerable populations. The COVID-19 pandemic sparked an alert about the absence of the use of fundamental human guarantees within women’s prisons, which was already characterized by the harsh reality of invisibility, therefore, this study aims to identify the impacts of the COVID-19 pandemic on enforcement of human rights and public health actions and services in penal establishments for women. This is a systematic review, which used productions collected in the database of the Virtual Health Library (BVS), Bank of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES), Scientific Electronic Library Online (SciELO), Oxford Academic (OXford - EBSCO), Google Scholar. Data collection was carried out from January to May 2022, covering publications between the years 2020 to 2022. No language restriction. The results were presented in three categories: (1) Main national and international legal norms on Human Rights in penal establishments; (2) Limitations on enforcing human rights actions in women’s prisons in the midst of a public health emergency; (3) The main violations notified about the guarantees provided for in the regulations presented. Some of the results point to the weakening of the application of human rights and the deepening of poverty, increasing inequalities, structural and entrenched discrimination and other gaps in the protection of the human rights of women in prison.